2010
DOI: 10.1080/15567030903059830
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cottonseed Oil–Kerosene Blends on a Diesel Engine Performance and Exhaust Emissions

Abstract: Nowadays, increasing crude oil prices and environmental pollution problems have lead to investigation of alternative fuel necessities, such as vegetable oils for internal combustion engines. This article presents the possibility of using cottonseed oil-kerosene blends in compression ignition engines. Engine performance and exhaust emissions were examined and diesel fuel was used as a basis for comparison. The influences of using various blended cottonseed oil-kerosenes on brake specific fuel consumption, exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Overall, K60P40 showed the highest ITE among all the test fuels, which can be attributed to its longer combustion duration and higher heat release rate. These findings are similar to the results of Bayindir, who reported that engine efficiency increased with the kerosene addition …”
Section: Resultssupporting
confidence: 92%
“…Overall, K60P40 showed the highest ITE among all the test fuels, which can be attributed to its longer combustion duration and higher heat release rate. These findings are similar to the results of Bayindir, who reported that engine efficiency increased with the kerosene addition …”
Section: Resultssupporting
confidence: 92%
“…The primary reason might be that the combustion efficiency of kerosene is higher than that of diesel due to its shorter combustion duration and resultant higher isovolumetric degree. Similar experimental results were reported that engine thermal efficiency increased with the kerosene addition [44]. Furthermore, the K80P20 presented lower ITE and higher ISFC than kerosene by 1%-6.5%, which was due to less complete combustion of K80P20 caused by its lower combustion efficiency.…”
Section: Fuel Economysupporting
confidence: 85%
“…The higher oxygen content of COME shows negative effects on the formation of smoke and particulate matter (PM) emissions, while the higher density and viscosity show opposite effects. As a result, for COME-diesel blends, the smoke and PM emissions are just slightly decreased when small amount of COME is added under the low-and middle-engine loads Bayindir 2010a, 2010b;Bayindir 2010;Hoda 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Cottonseed oil produced ETHYLENE GLYCOL MONOMETHYL ETHER COTTONSEED OIL MONOESTER 377 from cotton plants is one of the main vegetable oils supplied for food and other chemicals in China and other areas in the world. The formation, engine performance, as well as emission characteristics of biodiesels derived from cottonseed oil (mainly the cottonseed oil methyl ester (COME)) were widely investigated in most countries such as Brazil (Simoni, Mario, and Tatiana 2007), China (Yao, Ji, and Sun 2010), India (Syed, Raja, and Gopal 2009), Turkey Bayindir 2010a, 2010b;Bayindir 2010;Hoda 2010), the USA (Umer, Farooq, and Gerhard 2009), and so on. Previous studies indicated that, compared to diesel fuel, COME has lower UHC, CO, and SO x emissions, but higher NO x emission.…”
Section: Introductionmentioning
confidence: 99%